2021
DOI: 10.7759/cureus.13475
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome in a Patient With SARS-CoV-2 Infection Treated With Tocilizumab

Abstract: As the world has struggled to adapt to the coronavirus disease (COVID-19) pandemic, new evidence has emerged suggesting that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may manifest with a wide variety of neurologic symptoms. We present the case of a 70-year-old patient hospitalized for COVID-19 related pneumonia who was treated with off-label interleukin (IL)-6 inhibitor tocilizumab and eventually developed prolonged delirium. MRI findings were consistent with posterior reversible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Small foci of restricted diffusion in deep white matter. Present Present Discharged P30/M/70 Talluri K et al 43 Hypertensive Absent Present Absent Mechanical ventilation Tocilizumab Cortical and subcortical FLAIR signal in bilateral occipital lobes and paramedian frontal and parietal lobes. Restricted diffusion bilateral occipital lobes, posterior thalami and left temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
“…Small foci of restricted diffusion in deep white matter. Present Present Discharged P30/M/70 Talluri K et al 43 Hypertensive Absent Present Absent Mechanical ventilation Tocilizumab Cortical and subcortical FLAIR signal in bilateral occipital lobes and paramedian frontal and parietal lobes. Restricted diffusion bilateral occipital lobes, posterior thalami and left temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
“…Database search recovered 37 unique articles describing PRES and COVID‐19, of which five were excluded after abstract review. The remaining 32 articles underwent full text review; 22 articles met all inclusion criteria and contained detailed clinical information on 32 individuals with PRES and COVID‐19 [6–27]. All cases reported MRI findings consistent with a diagnosis of PRES (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Many cases had complete resolution of neurological issues by the time of publication, but approximately one third of individuals had residual problems including cognitive deficits, vision loss, and weakness (Figure 4b and Table 1). Death occurred in four (11%) cases (Figure 4b and Table 1) [6,18,23,25].…”
Section: Literature Searchmentioning
confidence: 99%
“…Increasing evidence supports the safety and efficiency of the IL-6 receptor blocker tocilizumab for treating patients with severe or critical COVID-19, especially those with cytokine release syndrome [ 189 191 ]. Case reports described that tocilizumab exerted potential beneficial effects on COVID-19-related neuropsychiatric symptoms, including encephalopathy presenting with aphasia and posterior reversible encephalopathy syndrome [ 192 , 193 ]. Case reports and case series showed that immunotherapy with intravenous immunoglobulin was safe and effective for the treatment of COVID-19-associated neurological disorders, including encephalopathy, GBS, and new-onset refractory status epilepticus [ 194 196 ].…”
Section: Strategies For Treatment Of Sars-cov-2-related Neuropsychiatric Complicationsmentioning
confidence: 99%